Law and firms' access to finance - Beck, Thorsten, 1967- 1967- (NBER working paper series, 2004)
"This paper contributes to the literature on how a country's legal origin influences the operation of its financial system by using firm-level survey data on the obstacles that firms face in raising external finance. The paper assesses two channels through which legal origin may influence the financial system. It finds that the adaptability of a country's legal system is more important for explaining the obstacles that firms face in accessing external finance than the political independence of the judiciary"--National Bureau of Economic Research web site